Convergent evolution of unusual complex I homologs with increased proton pumping capacity: energetic and ecological implications. Issue 11 (November 2018) - Chadwick, Grayson; Hemp, James; Fischer, Woodward; Orphan, Victoria
Abstract Respiratory complex I is part of a large family of homologous enzymes that carry out the transfer of electrons between soluble cytoplasmic electron carriers and membrane-bound electron carriers. These complexes are vital bioenergetic enzymes that serve as the entry points into electron transport chains for a wide variety of microbial metabolisms, and electron transfer is coupled to proton translocation. The core complex of this enzyme is made up of 11 protein subunits, with three major proton pumping subunits. Here, we document a large number of modified complex I gene cassettes found in genome sequences from diverse cultured bacteria, shotgun metagenomics, and environmentally derived archaeal fosmids all of which encode a fourth proton pumping subunit. The incorporation of this extra subunit into a functional protein complex is supported by large amino acid insertions in the amphipathic helix that runs the length of the protein complex. Phylogenetic analyses reveal that these modified complexes appear to have arisen independently multiple times in a remarkable case of convergent molecular evolution. From an energetic perspective, we hypothesize that this modification on the canonical complex I architecture allows for the translocation of a fifth proton per reaction cycle—the physiological utility of this modified complex is discussed.